Hofstede's Cultural Dimensions and Tourist Behaviors: A Review and Conceptual Framework - Manrai, Lalita A. (2011)
This paper develops a conceptual framework for analyzing tourist behaviors and identifies three categories of behaviors based on the applications of Hofstede's cultural dimensions and the processes underlying these influences. Our findings indicate that tourist behaviors in the Before-Travel During-Travel and After-Travel stages differ significantly in terms of the applicability and process through which Hofstede's cultural dimensions operate. The results of our analysis suggest three categories of behavioral patterns namely "Social Interaction Driven Travel Behaviors" (SID) "Risk Tendencies Driven Travel Behaviors" (RTD) and "Collectivity Orientation Driven Travel Behaviors" (COD). SID relates to the evaluation of travel experiences in the after-travel stage. The dominant cultural values associated with SID are Individualism/CollectivismMasculinity/Femininity and Power Distance. These three values act either independently or in pairs or all three together. RTD relates to the consumption of travel products in the during-travel stage and COD relates to the formation of travel preferences in the before-travel stage. Individualism/Collectivism and Uncertainty Avoidance are associated with both RTD and COD. However the underlying processes differ for these two categories of travel behaviors. In addition to their independent influences on travel behaviors these two values associated with RTD and COD also have an interactive effect. For RTD the Uncertainty Avoidance motive determines the Individualism/Collectivism outcome whereas for COD the opposite is true: the Individualism/Collectivism determines the Uncertainty Avoidance outcome. The paper also discusses the application of a fifth cultural dimension Confucian Dynamism (short-term versus long-term orientation) for the study of tourists' behaviors.